Filariasis Bancrofti Epidemiology Post Mass Drug Administration in Waris District Keerom Regency Province of Papua - Korinus Suweni; Soeyoko Soeyoko; Sri Sumarni (Tropical Medicine Journal, 2013)
ABSTRACTIntroduction: Filariasis remains to be world’s health problems including Indonesia. Based on survey conducted in 2009, the occurrence cases in Indonesia reached 11.914 chronic cases. Further, there were 59 chronic cases in Keerom Regency in 2005. The number of chronic filariasis cases in Waris District reached 25 cases, with 12 people were having positive microfilaria bancrofti.Objectives: The aim of study to find out epidemiology of filariasis bancrofti after collective treatment in  Waris District, Keerom Regency, Papua.Methods: This study used descriptive research with cross sectional design. Data are collected by finger blood survey, survey of acute morbidity rate, survey of chronic morbidity rate, microfilaria periodicity survey, and L3 examination on mosquitoes.Result : Survey finger blood taken from 517 samples show 32 positive microfilariae, and filariasis prevalence of 6.19%. There are 13 patients (2.15%) having acute symptoms of filariasis, and 24 patients (4.64%) have symptoms of chronic filariasis. From the examination and dissection of 358 mosquitoes, there are nolarvae stage 3 (L3). From 7 people having microfilaremia, there is periodic nocturnal of 71.43%  and subperiodic nocturnal of 28.57%.Conclusion: The prevalence of filariasis was 6.19%. There were 13 people having acute morbidity (2.51%), and there were 24 chronic morbidity (4.64%). There was no L3 found from dissected 358 mosquitoes. Periodicity of microfilariae in Waris District is periodic nocturnal which reach 71.43% and nocturnal subperiodik is28.57%.Keywords: Epidemiology, Filariasis, Finger Blood Survey